P143 Association between platelet count and pleural infection. (12th November 2019) - Dudina, AL; Bedawi, EO; Mercer, RM; George, V; Hallifax, R; Rahman, NM
Abstract : Introduction: Secondary thrombocytosis is one of the commonest reactive processes in clinical settings of acute bacterial and viral infection. Platelet response could be similar to any other markers of inflammation such as C-reactive protein (CRP) and white cell count (WCC). Objectives: The aim of this study was to analyse whether change in platelet counts could be associated with time of recovery in patients with pleural infection on day 7 as compared with day 1. What is the association of platelet count with other inflammatory markers? Subjects and methods: This was a retrospective study using data from MIST2 trial recorded in 11 centres in the UK within 3 years (2005–2008). 1 For our analysis there were available 25 patients in placebo group, 23 - in t-PA group, 21 patients in DNase group and 25 patients in t-PA and DNase group. We calculated the change in inflammatory markers in all groups of treatment. Paired t-test was applied to calculate the mean difference in platelets, CRP and WCC during recovery time. Spearman's rank test used for comparison of means in four groups of treatment. Results: The analysis revealed an increase in mean platelets count from 489.25±215 to 575.78±231 9/L (p=0.000) by day 7 in whole data population with the highest increase in tPA&Dnase group and slight fall in tPA arm (Figure 1). Platelets correlate negatively with WCC and CRP which decreased by 3.05 (p=0.000) and 76.29 (p=0.000) respectively. But there is a weak correlation with the decreased WCC and CRP in the group treated with tPA and DNase. Conclusion: The reaction of platelets seems to be stronger than reaction of other inflammatory markers during treatment with tPA&DNase arm. This might be due to interaction between these two medications or platelets fall more slowly during recovery. A better understanding of the platelets role in pleural infection might help to produce new prognostic and therapeutic approaches. Reference: Rahman NM, MN., West A, et al . Intrapleural use of tissue plasminogen activator and DNase in pleural infection. N Engl J Med 2011;365(6):518.